2015
DOI: 10.1002/ptr.5527
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Secondary Metabolites Synergize the Activity of Commercial Antibiotics against Clinical Isolates of β-Lactamase-producing Klebsiella pneumoniae

Abstract: Emergence of worldwide antimicrobial resistance prompted us to study the resistance modifying potential of plant-derived dietary polyphenols, mainly caffeic acid, ellagic acid, epigallocatechin-3-gallate (EGCG) and quercetin. These compounds were studied in logical combination with clinically significant antibiotics (ciprofloxacin/gentamicin/tetracycline) against Klebsiella pneumoniae, after conducting phenotypic screening of a large number of clinical isolates and selecting the relevant strains possessing ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Traditional Chinese green tea and its constituents have long been studied for antimicrobial properties. EGCG, for example, is reported to have growth inhibitory effects both against gram-positive and gram-negative bacteria, i.e., Staphylococcus aureus [ 7 , 8 , 9 ], Escherichia coli [ 10 ], Acinetobacter baumannii [ 11 ], and klebsiella pneumoniae [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese green tea and its constituents have long been studied for antimicrobial properties. EGCG, for example, is reported to have growth inhibitory effects both against gram-positive and gram-negative bacteria, i.e., Staphylococcus aureus [ 7 , 8 , 9 ], Escherichia coli [ 10 ], Acinetobacter baumannii [ 11 ], and klebsiella pneumoniae [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial strains usually were clinical isolates with a specific resistance (no full antibiogram reported). In the reviewed reports, the utilization of standard strains were the exception more than the rule (3% of the tested strains) [32][33][34][35][36][37][38][39][40] . In almost all the cases, resistant opportunistic bacteria were the target, the most frequently strain tested were clinical isolates of MRSA.…”
Section: Summary Of the Literature Review Resultsmentioning
confidence: 99%
“…Table 2: Summary of purified natural products screened for antibiotic modulatory effects of commercially available drugs against nosocomial bacteria, that yielded synergistic effects. For more details see text [32][33][34]46,47,51,70,71,[97][98][99][100][101] . is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Some studies have suggested the synergism between EGCG and different antibiotics on inhibiting bacteria like methicillin-resistant S. aureus (MRSA), P. gingivalis, and K. pneumoniae [22,69,70], and on bacterial biofilms. Biofilm formation by pathogenic organisms has developed tolerance to elevated levels of antimicrobials [71].…”
Section: Discussionmentioning
confidence: 99%